Solutions manual for quantitative chemical analysis - Harris, Daniel C. (W.H. Freeman and Company, 1998)
Contents: Measurements; Voltammetry; Fundamentals of spectrophotometry; Atomic spectroscopy; Introduction to analytical separations...